Effect of anemia on oral cavity and hematological assessments - Mahdi Idan, Hayder; Abdul-Mahdi Hasani, Rafid; Qahtan Othman, Ibtehal (Diyala Journal of Medicine, 2024)
Background: Anemia is a decrease in the amount of hemoglobin, or red blood cells, in the blood. Slow-onset symptoms, such as dyspnea, exhaustion, weakness, or impaired exercise capacity, are frequently nonspecific. Red blood cells' capacity to carry oxygen is limited by anemia. This suggests that the body's tissues and organs take less oxygen from the blood. Objective: To determine the effect of anemia on oral cavity in addition hematological assessments and compare them with healthy controls. Patients and Methods: Among 80 people, a cross-sectional study was conducted. Twenty healthy control participants (9 male and 11 female) and sixty patients with anemia (22 male and 38 female) made up the study samples. Study was directed in September 2023 in Alkhalis hospital-Diyala. Results: Level of hemoglobin in the control group showed a statistically highly significant increase with mean ± SE (14.12 ±0.35) as compared with patients’ group. The white blood cell counts showed an increase in the control group with mean ± SE (9.92 ±0.54) as compared with patients’ group, with a statistically highly significant correlation. Out of 60 patients, 2 (3.33%) were complaining from angular cheilitis, 6 (10%) were complaining from burning mouth syndrome, 5 (8.33%) were complaining from recurrent aphthous stomatitis, and 13 (21.67%) were complaining from atrophic glossitis, with a statistically highly significant relationship. Conclusion: Differences in white blood cell counts in patients with anemia and healthy control. Many oral manifestations associated with anemia such as atrophic glossitis, burning mouth syndrome, angular cheilitis, and recurrent aphthous stomatitis.